EARLY SYNTACTIC ACQUISITION IN A BALINESE SPEAKING CHILD - Adnyani, Ni Luh Putu Sri (Masyarakat Linguistik Indonesia, 2020)
This article addresses the acquisition of syntax in a Balinese monolingual child at the age of 2;5 until 2;7. The data was collected in natural setting when the child involved in spontaneous interaction with adults. The speech produced by the child was segmented based on the utterances. The speech produced by the child was transcribed orthographically, along with the phonetic transcription. Besides, every utterance produced by the child accompanied by contextual description and explanation. The data was coded and glossed according to the parts of speech, and grammatical functions. The results show that at this stage, even though the child goes through early sentence or word combinations stage, the child still produces single-word utterances at the onset as well. The words belong to noun, verb, adjective, adverb and particle. Words combination produced can be classified into declarative, interrogative, and imperative sentences. Initially, the child frequently omit subject. The fact that in colloquial adult?s conversation in Balinese omitting subject is acceptable may contribute to the subject omission. In two words combinations NP and VP occurred and in three or more words utterances S-P, S-P-O and S-P-C starting to be produced. In making questions kije?where?, ape ?what?, encen ?which one? and nyen ?whose? are used. In question, the child also applied rising intonation when question words are not applied. The child is also able to express tag question. In imperative sentences, the child is able to use command, request, and invitation. This study implies the role of adult?s input in children language acquisition as shown in subject omission and the flexible word order.